2013
DOI: 10.1364/oe.21.000445
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of water jet generated by Q-switched laser induced water breakdown with different depths beneath a flat free surface

Abstract: The dynamics of a water jet on a flat free surface are investigated using a nanosecond pulsed laser for creating an oscillating bubble with different depths beneath the free surface. A thin jet is shown to deform a crater surface resulted from surface depression and cause a circular ring-shaped crater on the connection surface between the crater of surface depression and the thin jet. The collapse of this circular ring-shaped crater is proposed to the crown-like formation around a thick jet. The evolution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Figure 5 shows the energy dispersive spectrometer (EDS, OCTANE SUPER-A, EDAX AMETEK, Mahwah, NJ, USA) analysis results at given sidewall positions. It seems that the intensity of oxygen (O) is slightly less in the semi-water-assisted trepanning results compared with the direct trepanning case, which may be attributable to the effective removal of the molten and oxide layers that are induced by laser irradiation via laser-caused mechanical effect in water, such as strengthened shockwaves and high-pressure waterjets originating from water-confined plasma expansion and dynamic bubble collapse [25,26,27,28]. Figure 6 depicts the exit details of the trepanning results, where it can be clearly seen that direct laser trepanning leads to a quite small exit, and therefore a large hole taper is expected, while SWILT is associated with a wider exit and hence a quite straight sidewall, although the roundness is not as good as in the direct trepanning case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the energy dispersive spectrometer (EDS, OCTANE SUPER-A, EDAX AMETEK, Mahwah, NJ, USA) analysis results at given sidewall positions. It seems that the intensity of oxygen (O) is slightly less in the semi-water-assisted trepanning results compared with the direct trepanning case, which may be attributable to the effective removal of the molten and oxide layers that are induced by laser irradiation via laser-caused mechanical effect in water, such as strengthened shockwaves and high-pressure waterjets originating from water-confined plasma expansion and dynamic bubble collapse [25,26,27,28]. Figure 6 depicts the exit details of the trepanning results, where it can be clearly seen that direct laser trepanning leads to a quite small exit, and therefore a large hole taper is expected, while SWILT is associated with a wider exit and hence a quite straight sidewall, although the roundness is not as good as in the direct trepanning case.…”
Section: Resultsmentioning
confidence: 99%
“…This results in a water-confined plasma zone and subsequent cavitation bubbles, leading to a strengthened mechanical effect and high-pressure micro-sized waterjet, where the pressure can be up to around several GPa. This is sufficient to cause the removal of the softened ceramic particles/powder [25,26,27,28], so that the rough ablated surface may be produced, as illustrated in Figure 12. Since the mechanical effect is stronger in tighter spaces, the material-removal rate near the exit side surpasses that of the upper position, so that a much straighter sidewall is expected, and thus a reduced hole tapering.…”
Section: Discussionmentioning
confidence: 99%
“…The bubble depth is defined in a dimensionless parameter γ = D/R max , where D is the bubble depth beneath the free surface and R max is the maximum bubble radius, as depicted in the schematic picture of figure 1(b). In our previous studies [11], we observed that a thin jet was initially generated in laser-induced breakdown and subsequently a thick jet with a crown-shaped cup was created. The mechanism of crown formation is an interesting topic.…”
Section: Methodsmentioning
confidence: 91%
“…The approaches for generating the bubble and the liquid jet include chemical and nuclear explosions, spark discharge and pulsed laser focusing. The advantage of using a laser-induced liquid jet over other methods is reproducibility and controllability [9,11,13,14]. The laser-induced liquid jet has been studied in film-free laser printing [9], volcanology [15] and biology and medicine [16].…”
Section: Introductionmentioning
confidence: 99%
“…Gas breakdowns generated by high-power optical pulses can be traced back to the groundbreaking era for lasers [1,2]. Since then, the technologies of laser-induced breakdowns (LIBs) have been intensely studied and developed to be mature applications, including laser ablation [3], micromachining [4], photochemistry [5], laser fusion [6], laser-induced breakdown spectroscopy [7], laser ignition [8,9], and cavitation bubble generation [10]. The LIB is generally described as the formation of ionized gas or plasma during or by the end of the excitation of the laser pulse.…”
Section: Introductionmentioning
confidence: 99%